Oral Health Survey at PPA Eagle and PPA Agape: Dental Health Status, Service Needs and WTP (Willingness to Pay) - Apri Adiari Manu; Rosliani Saragih (Poltekkes Kemenkes Kupang, 2024)
Low utilization of dental health services, particularly among children, is a significant public health issue. Factors such as distance, cost, and service quality hinder access. Child Development Centers (PPA) present a potential target population for dental health interventions. The objective of this study to assess the oral health status and service needs of PPA children, determine the Foundation's willingness to pay for dental treatments, and explore potential collaborations between the PPA and the Dental Health Department. The methods used a cross-sectional study was conducted on 522 PPA children. Data on oral health status, service needs, and willingness to pay were collected using a questionnaire and analyzed using statistical methods. The results of this study revealed a high prevalence of dental caries among children. The most common service need was dental fillings. The Foundation's willingness to pay for dental services was significantly lower than the current rates offered by the Dental Health Department. The conclusion is the findings highlight the need for affordable and accessible dental care for PPA children. Collaborations between the PPA and the Dental Health Department can help address this issue by providing subsidized or free dental services.